Optimum design of concrete structures - Bui Nguyen Nhac (Vietnam Journal of Mechanics)
One of the optimum design methods, concerned with the concrete structures, has just been presented. In order to obtain the optimum design, the solution of nonlinear mathematical programming problem has to be worked out. The amplification of the method was illustrated by a practical example.